Experiences and challenges of Non-Governmental Organizations (NGO)s professionals in ensuring the right to education for the Rohingya refugee children in Cox's Bazar - Sadia, Sumaiya (2022)
In 2017, a Myanmar government’s military operation forced 700,000 Rohingya to flee to Cox’s Bazar, Bangladesh. Forcibly Displaced Myanmar Nationals (FDMN) legal status limited the education access for the Rohingya children in Cox’s Bazar. Also, the education system is submerged in various socio-economic-political-infrastructural problems. This study explores the Bangladeshi humanitarian professional’s adopted educational approaches, interventions and the challenges in ensuring the right to education for the Rohingya children in Cox’s Bazar. Theoretically, the study is based on the Exile and Resettlement Theory, Dualist and Monist Theory of International Law and Resumption of an Ordinary Life. In this study, a qualitative research design was applied. Study participants were selected purposively through the snowball technique, and the data were collected through semi structured interviews from Bangladeshi nine humanitarian professionals. In analyzing the findings, thematic analysis method was used. The findings explored that Cox’s Bazar education sector provides informal education through the Learning Competency Framework and Approach (LCFA) curriculum. LCFA follows a standardized curriculum for refugee settings and consists of five subjects- Math, English, Science, Burmese Language, and Life Skills. The Myanmar Curriculum Piloting (MCP) is paving a new phase of secondary education for Rohingya children. The Bangladesh government’s restrictions on formal education, certification and technology access, language complexity, poor learning environment, gender inequalities, lack of trained teachers, current COVID-19 situation, and many other challenges hinder Rohingya education. The Cox’s Bazar Education sector adopted various strategies to mitigate the challenges in different levels of Rohingya community.